2020
DOI: 10.4054/demres.2020.42.28
|View full text |Cite
|
Sign up to set email alerts
|

Are sibling models a suitable tool in analyses of how reproductive factors affect child mortality?

Abstract: A mathematical argument 3 Methods 3.1 Estimation of effect parameters to use in the simulation 3.2 Simulation 3.3 Estimation of mortality models from the simulated population 3.4 Replications 4 Results 4.1 Assuming that there is no effect of earlier infant death on fertility 4.2 What happens if there 'in reality' is an effect of earlier infant death on fertility? 4.3 Generally higher fertility or mortality 4.4 Alternative assumptions about effects of maternal age, birth interval, and birth order in the simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Families that experience multiple infant deaths are strongly selected, and this is particularly true in a low-mortality context. Recent research has also highlighted the possibility that offspring deaths change the fertility behavior of parents, meaning that the length of the birth interval itself is influenced by the death of the preceding sibling; when the outcome for one sibling influences the exposure for another, sibling fixed effects models may be biased (Sjölander et al, 2016;Kravdal, 2020). This is particularly likely for infant mortality, but may also be true for our analyses of LBW and preterm, and is an important limitation of the sibling comparison analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Families that experience multiple infant deaths are strongly selected, and this is particularly true in a low-mortality context. Recent research has also highlighted the possibility that offspring deaths change the fertility behavior of parents, meaning that the length of the birth interval itself is influenced by the death of the preceding sibling; when the outcome for one sibling influences the exposure for another, sibling fixed effects models may be biased (Sjölander et al, 2016;Kravdal, 2020). This is particularly likely for infant mortality, but may also be true for our analyses of LBW and preterm, and is an important limitation of the sibling comparison analyses.…”
Section: Discussionmentioning
confidence: 99%
“…A simulation has shown that the bias may be huge. 5 There is apparently inadequate awareness of the linear-dependence and…”
Section: Response To Letter: Sibling Models-an Underused Tool With Limitationsmentioning
confidence: 99%
“…At each month (t) until the woman turned 45, probabilities of first (f 1tj ) and higher-order (f 2tj ) births were predicted from the logistic equations where A tj , D tj and P tj are categorical variables representing age, time since last birth, and parity, respectively, and σ j is the fertility random term. The coefficients (ie the αs and βs) were taken from an earlier study 13 and reflect patterns actually observed in Norway, but subjected to visual smoothing. The variables A tj , D tj , and P tj were updated monthly as the simulation "proceeded.…”
Section: Ta B L E 2 Effects Of Birth Interval and Birth Order On Infant Mortalitymentioning
confidence: 99%
“…For each month, a number was drawn from a uniform distribution over [0,1], and if this number was smaller than the relevant predicted birth probability, a birth (up to a fifth, as few have more children in Norway) was assigned to the woman that month. In that case, the probability that this child died within 12 months was predicted from the relevant demographic variables multiplied by coefficients taken from the mentioned earlier study 13 (except that a larger intercept was used to get a larger number of deaths), and with a mortality random term added-in parallel with the predictions of fertility. In mathematical terms, the prediction equation for the death probability m ij for child i of mother j was:…”
Section: Ta B L E 2 Effects Of Birth Interval and Birth Order On Infant Mortalitymentioning
confidence: 99%
See 1 more Smart Citation